2009
DOI: 10.1007/s10947-009-0103-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of complexation of pesticides (fenitrothion, methylparathion, parathion) and their carboxylic ester analogues by β-cyclodextrin. Theoretical semiempirical calculations

Abstract: The complexation by -cyclodextrin ( -CD) of three organophosphorus pesticides, fenitrothion, parathion and methylparathion, and of their carboxylic ester analogues was analyzed using PM3 and molecular mechanics methods. The objective was to elucidate structural features and energy changes that accompany the complexation and could possibly affect the hydrolysis process, which is catalyzed by -CD in the case of carboxylic esters but inhibited for the pesticides, in alkaline medium. The complexation of fenitrothi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Indeed the two latter can form deeply included complexes (high α in parameter) compared to fenitrothion which is therefore less shielded from hydroxide ions, leading to the highest hydrolysis rate observed in this series ( Table 3 ) [ 42 ]. The origin of this trend was disclosed by theoretical semi-empirical calculations of parathion-, methyl parathion- and fenitrothion-β-CD complexes [ 55 ]. It was shown that the methyl group, adjacent to the nitro function slightly impairs both deep and axial inclusion of fenitrothion into the cavity.…”
Section: Reviewmentioning
confidence: 99%
“…Indeed the two latter can form deeply included complexes (high α in parameter) compared to fenitrothion which is therefore less shielded from hydroxide ions, leading to the highest hydrolysis rate observed in this series ( Table 3 ) [ 42 ]. The origin of this trend was disclosed by theoretical semi-empirical calculations of parathion-, methyl parathion- and fenitrothion-β-CD complexes [ 55 ]. It was shown that the methyl group, adjacent to the nitro function slightly impairs both deep and axial inclusion of fenitrothion into the cavity.…”
Section: Reviewmentioning
confidence: 99%
“…9,15,17 Theoretical calculation of the energies of the two types of complexes indicates that in the gas phase there is no significant difference in their values. 18 Therefore it is likely that the permethylation of the rim of the b-CD (TRIMEB) changes the combination of interactions between the host and the guest which results in a change of guest orientation in the cavity.…”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…This was suggested for parathion, methyl parathion, and paraoxon [17,21,23]. Theoretical calculation of the energies of the two types of complexes in the gas phase indicates that there is no significant difference in their values [24]. Single-crystal X-ray analysis shows that for β-CD and TRIMEB, complexes of type A are formed while for DIMEB (see above) in the unit cell a small percentage of the inclusion complexes exhibit the type B orientation.…”
Section: Resultsmentioning
confidence: 99%